The summer skies : [large type] a novel - Colgan, Jenny (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
Running an island plane service with her grandfather on the remote islands of northern Scotland, Morag McGinty, on the verge of making a huge life change, is marooned on an off-grid island with a visiting ornithologist who has just the right perspective to help her pilot her course.